Corporate Social Responsibility: dependence of commercial success on social initiatives - Abdimomynova, A.Sh.; Duzelbaeva, G.B.; Berikbolova, U.D.; Karbozova, A.S.; Mukhtarova, А.М. (BUKETOV BUSINESS REVIEW, 2023)
Object: This study aims to identify the relationship between the economic results of a company and its participation in solving social problems. Modern business conditions require companies to use fundamentally new methods of drawing the attention of consumers and counterparties to their activities. One of the ways to positively influence the reputation of companies is to provide them with additional benefits. Among other things, these benefits include advantages offered by social initiatives. Corporate social responsibility (CSR) is becoming a necessary condition for compliance of a business with international standards. The global scientific community has given rise to long discussions about the impact of CSR on the financial results of companies’ activities. This particular issue has determined the relevance of the present research topic. Methods: By applying economic and mathematical methods, the paper outlines the dependence between enterprises’ economic outcomes and investment in social projects. Findings: The article analyzes data on ten large enterprises of the Republic of Kazakhstan participating in the implementation of social initiatives. Conclusions: By means of regression analysis, the paper has found a strong correlation between CSR expenditures, gross margin, profit, and turnover. Therefore, to strengthen market positions, it is advisable for companies to pay increased attention to solving internal and external social problems. This will contribute to strengthening the image of the enterprise, enhance its competitiveness and, as a result, financial performance. The results of the study can be used by enterprise managers to substantiate CSR development strategies.